2018
DOI: 10.1080/19476337.2018.1474265
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of milk quality during storage based on DNA extracted from milk

Abstract: This study investigated the changes of DNA and milk quality during storage at temperatures of 2°C, 10°C and 20°C. Milk quality was assessed by measuring the milk protein, milk fat, lactose, pH and acidity. The quality of DNA extracted from milk was evaluated by monitoring DNA content, purity, and degradation as well as by amplifying target sequences from mitochondrial and nuclear genes. In addition, nonlinear regression models were used to analyze the correlations between DNA content and milk quality. As expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The study by O'Callaghan, et al [16] investigated the influence of four supplemental feed choices for pasture-based cows on the fatty acid and volatile profile of milk. Some studies have also evaluated the effect of storage conditions on the microbiological quality of milk [17,18]. In the present study, the volatile profile and free fatty acid (FFA) content of the milk samples were evaluated over a 14-day storage period at 4 • C in order to ascertain the level of lipid oxidation occurring within the milk, and to track volatile compounds forming or changing during refrigerated storage.…”
mentioning
confidence: 99%
“…The study by O'Callaghan, et al [16] investigated the influence of four supplemental feed choices for pasture-based cows on the fatty acid and volatile profile of milk. Some studies have also evaluated the effect of storage conditions on the microbiological quality of milk [17,18]. In the present study, the volatile profile and free fatty acid (FFA) content of the milk samples were evaluated over a 14-day storage period at 4 • C in order to ascertain the level of lipid oxidation occurring within the milk, and to track volatile compounds forming or changing during refrigerated storage.…”
mentioning
confidence: 99%
“…The quality and quantity of the DNA extracted from dairy production is the key factor to the success of PCR methods used in dairy adulteration identification. Many factors, such as somatic cell number, milk composition, and DNA extraction methods, can affect the quality and quantity of the DNA used in PCR methods, and in turn, affect the adulteration detection effectiveness [19,20]. Many factors might affect the concentration of somatic cells in dairy products such as milk-producing animal breeds, lactation stage, and health as well as environments [21,22].…”
Section: Dna Extraction Methodsmentioning
confidence: 99%
“…So the UHT treatment may also result in DNA degradation and subsequently increase the difficulty of DNA detection. On the other hand, it was suggested that storage shows a significant influence on the DNA extracted from raw milk (Liao et al, 2018c), so there might be DNA degradation during the storage of UHT milk. Considering that monitoring the changes of DNA in UHT milk during storage not only contributes to optimizing DNA-based analysis methods but also provides a way to distinguish UHT milk composition in other dairy products.…”
Section: Introductionmentioning
confidence: 99%